2017
DOI: 10.1111/jgh.13790
|View full text |Cite
|
Sign up to set email alerts
|

Systematical analyses of variants in DNase I hypersensitive sites to identify hepatocellular carcinoma susceptibility loci in a Chinese population

Abstract: Our results indicated that rs12309362 (G > A), rs9970827 (A > G) in DHSs, and elevated expression of CEBPB were associated with a decreased risk of HCC. These results may contribute us to understand the function of regulatory DNA sequences in HCC development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Among them, rs62331150 was associated with the expression of tet methylcytosine dioxygenase 2 (TET2) in normal breast tissue and tumor tissue. Two new SNP (rs12309362 and rs9970827) were found to be significantly associated with reducing the risk of hepatocellular carcinoma (HCC) by measuring the mutations at the peak of DHSs in 1,538 patients with HCC and 1,465 normal controls (57).…”
Section: Dhss and Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, rs62331150 was associated with the expression of tet methylcytosine dioxygenase 2 (TET2) in normal breast tissue and tumor tissue. Two new SNP (rs12309362 and rs9970827) were found to be significantly associated with reducing the risk of hepatocellular carcinoma (HCC) by measuring the mutations at the peak of DHSs in 1,538 patients with HCC and 1,465 normal controls (57).…”
Section: Dhss and Diseasesmentioning
confidence: 99%
“…These two SNP sites were found to be in linkage disequilibrium with rs9790517 of the adjacent TET2 gene (55). It was also found that, in samples with mutation at the rs12309362 and rs9970827 sites, the risk of being affected with HCC decreased significantly (57).…”
Section: Dhss and Diseasesmentioning
confidence: 99%